35. WORK MOTIVATION OF HEALTHCARE STAFF AT SON UYEN GENERAL HOSPITAL, BAC GIANG PROVINCE IN 2025 (Vietnam Journal of Community Medicine, 2025)
Objective: Describe the work motivation of medical staff at Son Uyen General Hospital, Bac Giang province in 2025.Method: Cross-sectional descriptive design of 205 medical staff working at Son Uyen General Hospital from March 2025 to May 2025.Results: General work motivation of medical staff accounts for 59%. Regarding work motivation factors: training and development factors have the highest work motivation, accounting for 65.9%, achievement recognition factors have the lowest work motivation, accounting for 54.1%. Regarding work maintenance factors: management and supervision factors have the highest motivation, accounting for 63.9%, and income factors have the lowest motivation for work, accounting for 49.8%.Conclusion: The proportion of medical staff at Son Uyen General Hospital with general work motivation is quite good (59%), in which the work motivation factor is 62%, the work maintenance motivation is 58.5%.
Keywords: Work motivation; motivating factors; maintenance factors.